Promoting millet, an underutilized crop. A review of food-based approach in combating micronutrient deficiency - ILO, Jumoke; Famakinwa, Abiodun (Revista Colombiana de Investigaciones Agroindustriales, 2022)
Malnutrition of micronutrients is a global problem that is more serious than hunger and has lasting consequences for societies. This study reviews existing interventions, where traditional grains are being promoted to establish their importance and promote their use as food. It examines a sample of existing literature, highlights, some key takeaways, and identifies knowledge gaps and research objectives in order to solve the global problem of micronutrient deficiency. A more recent method is to use revolutionary food processing processes to produce micronutrient-rich meals using underutilized or local food crops like millet, which can prevent numerous micronutrient deficits at the same time without the risk of antagonistic interactions or nutrient loss.